Innovative Marketing Services in Business Practice - Katarzyna Bachnik; Robert Nowacki (Contemporary Economics, 2024)
Businesses embrace a tremendous shift towards service-dominant logic in order to achieve and sustain advantage. To expand its influence, marketing needs to take on a service lens as well. The customer-centric approach tries to position value generation with processes that al-low customers to "get things done", which is linked with a quest for innovation. Modern marketing takes an integrative approach - by trying to link various channels, touchpoints, and customer relationships - which both caters to organizational goals and fulfils customer expec-tations and aims at persuading and affecting behaviors rather than attitudes. The paper reports the theory of marketing service innovation and examines research data on how enterprises use marketing services, how they define their innovativeness, and perceive them as value generators. The authors break marketing services into advertising ser-vices and market-research services. Intense competition characterizes both. The analysis co-vers small, medium, and large companies in Poland. The main conclusions are: (a) the level of service innovativeness depends on a company context (its size, scope of operations, and busi-ness locations); (b) enterprises evaluate marketing services which they can access as generally innovative and potentially beneficial.
Keywords: M3; M31; O3; 330; marketing services; advertising services; research services; innovation; innovative marketing